Microbial biomass carbon in Oxisol determined by wet oxidation and combustion at high temperature - de Souza, Leandro Moraes; Sousa, Djalma Martinhão Gomes de; Reis Júnior, Fábio Bueno dos; Mendes, Ieda Carvalho (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the relationships between the methods of wet oxidation and the combustion at high temperature, used in determinations of microbial biomass carbon, and to verify the necessity of using correction factors between the two methods. Ninety‑six soil samples, collected at 0–10-cm soil depth in clayey Oxisol of the Cerrado region, under annual crops, pastures, eucalyptus, and native vegetation were used. The microbial biomass carbon was determined from K2SO4 extracts, using the fumigation‑extraction method, by wet oxidation with potassium dichromate and external heating, and by combustion at high temperature in a total organic C analyser. A significant, positive, linear relationship between the contents of organic C, determined by the two methods, was observed. The combustion at high temperature method detects, on average, 6.3% more organic C than the wet oxidation method.
Keywords: carbon analyzer; bioindicators; organic carbon; fumigation‑extraction; soil quality